Sixth Finger and Home Automation for Disabled Persons - Amrutha Biju; Vinija Kurian (Journal of Electronic Design Engineering, 2017)
A Home Automation System for Disabled Persons is proposed in this study. The proposed system gives a direct communication path between the external computing devices and human brain. This system converts human thought into action without the usage of muscles. Our proposed technology can be used by persons with disabilities in order to improve their capabilities and independence at home. The idea is based on the fact that brain will respond to various actions differently. The recorded brain signals are sent to the computer to extract specific signal features. Those features are then translated into commands to operate all appliances at home. The main idea is to support disabled persons. Here, we introduce a feature called sixth finger whose action is similar to a hand. According to the thought each action will takes place. Here, as a sample, signals similar to brain signals are generated in the matlab and processed to perform desired action.